Z ' s in neutrino scattering at DUNE - Ballett, Peter; Hostert, Matheus; Pascoli, Silvia; Perez-Gonzalez, Yuber F. [UNESP]; Tabrizi, Zahra; Funchal, Renata Zukanovich (Amer Physical Soc, 2019)
Novel leptophilic neutral currents can be tested at upcoming neutrino oscillation experiments using two complementary processes, neutrino trident production and neutrino-electron (nu - e) elastic scattering. Considering generic anomaly-free U(1) extensions of the Standard Model, we discuss the characteristics of nu - e scattering as well as e(+)e(-) and mu(+)mu(-) trident production at the DUNE near detector in the presence of such beyond the Standard Model scenarios. We then determine the sensitivity of DUNE in constraining the well-known L-e - L-mu and L-mu - L-tau models. We conclude that DUNE will be able to probe these leptophilic models with unprecedented sensitivity, covering unproved explanations of the (g-2)(mu) discrepancy.